Preparation and characterization of recycled high-density polyethylene hybrid composites for weathering and thermal aging performance - Narayanan, Thinakaran (2025)
This research focuses on the preparation and characterization of recycled high-density polyethylene (rHDPE)/calcium carbonate (CaCO₃) hybrid composites reinforced with fiberglass (FG) and waste rubber (WR), targeting structural applications in agricultural and outdoor environments. Objective 1 optimized the single-screw extrusion process using a twolevel full factorial Design of Experiments (DOE), identifying optimal conditions as 260°C mixing temperature, 20 rpm screw speed, and an 80:20 wt% ratio of rHDPE to CaCO₃, achieving improved mechanical properties, tensile strength of 18.89 MPa, flexural strength of 48.89 MPa, and compressive strength of 10.43 MPa. Objective 2 evaluated the effects of hybrid fillers on mechanical, thermal, flammability, and physical properties, revealing that FG significantly enhanced structural strength with a tensile strength of 12.6 MPa, while WR improved impact resistance and toughness. UL 94 flammability tests showed that FG 7030 achieved the shortest burn times (17.24 s for 25 mm and 110.78 s for 100 mm), and Limiting Oxygen Index (LOI) values increased from 18.5% for pure rHDPE/CaCO₃ to 37.78% for FG 6040, indicating enhanced flame retardancy. Thermogravimetric analysis (TGA) confirmed improved thermal stability with a decomposition onset temperature of 481.3°C, while DSC results showed good crystallinity retention, confirming minimal thermal degradation. FTIR analysis revealed chemical interactions between the matrix and fillers through carbonyl (C=O) and silicate (Si–O–Si) bonding, which improved interfacial adhesion. XRD patterns confirmed the preservation of crystallinity in the rHDPE matrix and effective integration of fillers without disrupting the lattice structure. Objective 3 assessed the outdoor performance under natural weathering and accelerated thermal conditions, where the selected formulation (70% rHDPE/CaCO₃, 21% FG, 9% WR) maintained its mechanical and thermal stability after 90 days of exposure, with only minor degradation observed in tensile strength (from 12.8 MPa to 12.6 MPa). FESEM analysis confirmed consistent filler dispersion and strong interfacial bonding. Overall, hybrid filler reinforcement significantly enhances the mechanical, thermal, and environmental resilience of rHDPE-based composites. By effectively utilizing recycled and industrial waste materials, this study offers a sustainable, high-performance alternative for structural use in construction, agriculture, and automotive industries.